Desain Ergonomis Kursi Kuliah Untuk Mahasiswa Kidal: Integrasi Analisis Antropometri dan Rapid Upper Limb Assesment - Yuselin, Nensi; Setiawan, Indra; Zahabiyah, Rifdah; Rosyidi, Edwar; Aisa, Neilinda Novita; Sidik, Pramana; Faizin, Deni Nur; Dewani, Thalita (Jurnal Media Teknik dan Sistem Industri, 2024)
Learning facilities such as chairs are learning tools that must be available to facilitate teaching activities. This can affect concentration and productivity in the learning process in the classroom. Astra Polytechnic is a private vocational college that implements a lecture time system of 8 hours per day. The length of the learning process is not supported by adequate facilities such as not having chairs specifically designed for left-handed students. In fact, the number of left-handed people reached 20 people in 2023 or 2.5% of the total students. Based on initial observations through sampling interviews with several left-handed students, this makes it difficult for students to write. In addition, the existing chairs do not match the dimensions of the students' body posture. The purpose of this study is to improve the ergonomic value of lecture chairs for left-handed students by considering the components and dimensions of the appropriate product. Improvements were made by creating an ergonomic chair design and making a prototype. After that, the process was evaluated using the Rapid Upper Limb Assessment (RULA) method. The results of the study were in the form of a prototype ergonomic design of a lecture chair for left-handed students with dimensions that had been adjusted by considering replacing the backrest and seat to be softer. The evaluation results show a value of 3 or are included in the "Medium" category so that they are worthy of being produced and used for the learning process at Astra Polytechnic. Fasilitas pembelajaran seperti kursi adalah sarana pembelajaran yang harus tersedia untuk melancarkan kegiatan pengajaran. Hal ini dapat mempengaruhi konsentrasi dan produktivitasnya dalam proses belajar di kelas. Politeknik Astra merupakan perguruan tinggi swasta berbasis vokasi yang menerapkan sistem waktu perkuliahan selama 8 jam per hari. Lamanya proses pembelajaran belum didukung oleh fasilitas yang memadai seperti belum memiliki kursi yang didesain khusus untuk mahasiswa kidal. Padahal jumlah penyandang kidal mencapai 20 orang di tahun 2023 atau sebesar 2,5% total mahasiswa keseluruhan. Berdasaran observasi awal melalui wawancara sampling terhadap beberapa mahasiswa kidal, hal tersebut membuat mahasiswa mengalami kesulitan dalam menulis. Selain itu, kursi yang sudah ada belum sesuai dengan ukuran dimensi postur tubuh mahasiswa. Tujuan dari penelitian ini adalah meningkatkan nilai ergonomis pada kursi kuliah untuk mahasiswa kidal dengan mempertimbangkan komponen penyusun dan dimensi produk yang sesuai. Perbaikan dilakukan dengan membuat rancangan desain kursi ergonomis dan membuat prototipenya. Setelah itu, proses dievaluasi menggunakan metode Rapid Upper Limb Assessment (RULA). Hasil penelitian berupa prototipe desain ergonomis kursi kuliah untuk mahasiswa kidal dengan dimensi yang telah disesuaikan dengan mempertimbangkan penggantian sandaran dan tempat duduk menjadi lebih empuk. Evaluasi hasil menunjukkan nilai 3 atau termasuk dalam kategori “Sedang” sehingga layak diproduksi dan digunakan untuk proses pembelajaran di Politeknik Astra.